2023
DOI: 10.3389/fped.2023.1132296
|View full text |Cite
|
Sign up to set email alerts
|

GHRH-GH-IGF1 axis in pediatric Down syndrome: A systematic review and mini meta-analysis

Abstract: ObjectiveTo analyze and determine the quality of functioning in different components of GHRH-GH-IGF1 axis in children with Down syndrome (DS).DesignSystematic review and mini meta-analysis of the literature.MethodsA search was performed in PubMed, Embase, Scopus, and PsycINFO through August 2022. Eligible studies included pediatric patients with DS who had undergone any laboratory evaluation of the GHRH-GH-IGF1 axis. Two reviewers independently screened articles for eligibility. Results of each type of test we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have reported a certain degree of impairment of the GHRH-GH-IGF1 axis in subjects with trisomy 21. In detail, some authors have highlighted that short stature in DS can result from a combination of unsatisfactory hypothalamus–pituitary secretion and reduced bioactivity of endogenous GH ( 76 ).…”
Section: Auxologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported a certain degree of impairment of the GHRH-GH-IGF1 axis in subjects with trisomy 21. In detail, some authors have highlighted that short stature in DS can result from a combination of unsatisfactory hypothalamus–pituitary secretion and reduced bioactivity of endogenous GH ( 76 ).…”
Section: Auxologymentioning
confidence: 99%
“…The recurrent lack of controls, the limited follow-up, as well as the heterogeneous outcomes among treated patients has led to poorly reproducible conclusions ( 77 ). A recent meta-analysis reports a short-term efficacy of rhGH treatment on the growth of children with DS, irrespectively of endogenous GH secretion patterns ( 76 ). Nevertheless, most studies did not manage to demonstrate a longer-lasting and durable positive effect of the treatment on growth attainment ( 78 80 ).…”
Section: Auxologymentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity results in decreased GH and IGF-1 secretion ( 2 ), and it is more severe in patients with DS than in the general population ( 3 ). Reports indicate that patients with DS may have hypothalamic GH deficiency (GHD), which results from an impaired GH-releasing hormone (GHRH)–GH–IGF-1 axis ( 3 ). However, changes in hypothalamic GHD in adults with DS following weight loss remain unknown.…”
Section: Introductionmentioning
confidence: 99%